Relationship Between Leukocyte Esterase and Nitrite in Urine in Patients with Urinary Tract Infections at Suai Referral Hospital Covalima Timor-Leste - Gomes, Juvita Da Costa; Prihatiningsih, Diah; Abadi, Moh. Fairuz (CV. Publikasi Indonesia, 2025)
Urinary tract infections (UTIs) represent a significant healthcare concern, particularly among females. Accurate diagnosis is imperative to prevent complications associated with UTIs. The urinalysis procedure, often referred to as dipstick analysis, serves as a preliminary screening test for the identification of UTIs. This analysis typically examines two parameters: leukocyte esterase and nitrite. However, these parameters exhibit varying degrees of sensitivity and specificity in detecting UTIs. This study aims to ascertain the relationship between leukocyte esterase and nitrite in the urine of patients with UTIs. An observational analytical design with a cross-sectional approach was adopted. Samples were randomly selected from a cohort of 50 patients diagnosed with UTIs at Suai Referral Hospital in Covalima, Timor-Leste. Data were analyzed using the chi-square test in SPSS. The results indicated that 80% of UTI patients were leukocyte esterase–positive, while the remaining 20% were negative. Furthermore, 50% were nitrite-positive, and the remaining 50% were negative. Statistical analysis revealed no significant association between the presence of leukocyte esterase and nitrite in the urine of UTI patients (p = 0.480; p > 0.05). Consequently, no statistically significant relationship was identified between leukocyte esterase and nitrite levels in the urine of UTI patients. Therefore, urine dipstick examination should be complemented by more precise methods, such as urine culture, to ensure a more accurate diagnosis.